Managing Shariah non-compliance risk via Islamic dispute resolution - Maria Bhatti (Journal of Risk and Financial Management, 2020)
This article discusses Shariah non-compliance risk as a form of operational risk intending to ensure that operations in the Islamic and banking finance industry comply with Shariah procedures. In the field of Islamic finance, Shariah non-compliance risk refers to the possibility that Islamic finance transactions may be challenged based on Shariah non-compliance. This article uses a comparative and normative approach as well as a legal analysis of the case of Beximco. The article proposes the management of Shariah non-compliance risk by augmenting the effectiveness of Shariah governance systems with Islamic banking and finance arbitration; arbitration should be an enforced part of Islamic finance institutional arrangements—as it always has been classically—to provide flexibility for dispute resolution. To this end, the article examines contemporary implementations of Shariah arbitration rules to assess how Shariah non-compliance risk can be better managed via Islamic dispute resolution procedures.
Keywords: 330; i-arbitration rules; Islamic dispute resolution; Shariah governance; Shariah non-compliance risk